Impact of internal control on the efficiency of payroll management: case study of the Polytechnic School of Chimborazo - ESPOCH. - Vistín Mayorga, Verónica; Tapia Hermida, Ligia (mktDESCUBRE; Vol 1 No 24 (2024): Twenty-fourth Edition (July - December)DO - 10.36779/mktdescubre.v1i24.869, 2024)
Internal control is developed in all of institutions from the public sector to guarantee reasonable security in the fulfillment of their objectives and the reduction of risks. This research aimed to determine the impact of internal control on the efficiency of payroll management at ESPOCH between 2019 and 2023. To do this, a mixed approach study (qualitative-quantitative) was chosen to comprehensively address numerical elements. and qualitative interpretations and through this establish the relationship between the study variables. As data collection techniques, an interview was conducted with the Payroll Coordinator through which it was learned that internal control was mainly evaluated by the State Comptroller General's Office, in that sense information was collected from the special Audit examinations; As measurement instruments, control questionnaires were used that made it possible to measure the internal control of the application of technical budgetary remuneration standards. The results revealed that the level of confidence in the internal control of the remuneration budgetary regulations is high and affects the efficiency of remuneration and payroll management, showing that there is a close relationship between the study variables.